In uveal melanoma Gα-protein GNA11 mutations convey a shorter disease-specific survival and are more strongly associated with loss of BAP1 and chromosomal alterations than Gα-protein GNAQ mutations. (July 2022) - Piaggio, Francesca; Croce, Michela; Reggiani, Francesco; Monti, Paola; Bernardi, Cinzia; Ambrosio, Marianna; Banelli, Barbara; Dogrusöz, Mehmet; Jockers, Ralf; Bordo, Domenico; Puzone, Roberto; Viaggi, Silvia; et al.
Abstract: Background and aim of the study: Mutations in the Gα-genes GNAQ and GNA11 are found in 85–90% of uveal melanomas (UM). Aim of the study is to understand whether the mutations in both genes differentially affect tumor characteristics and outcome and if so, to identify potential mechanisms. Methods: We analyzed the association between GNAQ and GNA11 mutations with disease-specific survival, gene expression profiles, and cytogenetic alterations in 219 UMs. We used tandem-affinity-purification, mass spectrometry and immunoprecipitation to identify protein interaction partners of the two G-proteins and analyzed their impact on DNA-methylation. Results: GNA11 mutation was associated with: i) an increased frequency of loss of BRCA1 -associated protein 1 ( BAP1 ) expression (p = 0.0005), ii) monosomy of chromosome 3 (p < 0.001), iii) amplification of chr8q (p = 0.038), iv) the combination of the latter two (p = 0.0002), and inversely with v) chr6p gain (p = 0.003). Our analysis also showed a shorter disease-specific survival of GNA11 -mutated cases as compared to those carrying a GNAQ mutation (HR = 1.97 [95%CI 1.12–3.46], p = 0.02). GNAQ and GNA11 encoded G-proteins have different protein interaction partners. Specifically, the Tet Methylcytosine Dioxygenase 2 ( TET2 ), a protein that is involved in DNA demethylation, physically interacts with the GNAQ protein but not with GNA11, as confirmed by immunoprecipitation analyses. High-risk UM cases show a clearly different DNA-methylation pattern, suggesting that a different regulation of DNA methylation by the two G-proteins might convey a different risk of progression. Conclusions: GNA11 mutated uveal melanoma has worse prognosis and is associated with high risk cytogenetic, mutational and molecular tumor characteristics that might be determined at least in part by differential DNA-methylation. Highlights: GNA11 mutations are associated with increased risk of death in uveal melanoma. GNA11 mutated uveal melanoma shows high risk cytogenetics and gene expression. GNAQ but not GNA11 protein physically interacts with the demethylating enzyme TET2. GNAQ and GNA11 mutated uveal melanoma shows different DNA-methylation patterns.